Pension regimes and saving - Mackenzie, George A. (Internat. Monetary Fund, 1997)
enth.
Literaturverz. S. 41 - 43
Keywords: Graue Literatur; Pension trusts; Old age pensions; Saving and investment; Defined benefit pension plans; Gesetzliche Rentenversicherung; Rentenfinanzierung; Sparen; Rentenpolitik; Welt; Altersversorgung; Rentenversicherung; Rente; Finanzierung; Reform; Wirtschaftsreform; Vermögensbildung; Privatisierung; Altersstruktur; Sozialpolitik